Task Forces on Housing and Urban Development, IV Shelter for the Urban Poor and Slum Improvement - Planning Commission (Planning Commission, 1983)
In order to examine issues related to the Strategy for Housing and Urban Development, the Planning Commission has decided to appoint four Task Forces so that policies and programmes in this field may be formulated with a proper perspective in the Seventh Five Year Flan. The Task Forces are as follows: Task Force on Planning of Urban Development. Task Force on Financing of Urban Development. Task Force on Management of Urban Development. Task Force on Shelter for the Urban Poor and Slum Improvement. The composition and terms of reference for each Task Force are given in the Annexures ‘A’ to ‘D’. Non-official members of the Task Forces shall be entitled to TA|DA as permissible to Grade-I officers of the Government of India and will be paid by the Planning Commission. TA|DA to official members will be paid by their parent departments. The Task Forces 'are requested to furnish their final reports to the Planning Commission by June 15, 1983. All correspondence to these Task Forces may be addressed to Dr. Rakesh Mohan, Consultant, Planning Commission, New Delhi.
Shelter for the Urban Poor and Slum Improvement
Government of India